Fetal exposure to bisphenol A as a risk factor for the development of childhood asthma: an animal model study - Nakajima Yoichi; Goldblum Randall M; Midoro-Horiuti Terumi (BMC, 2012)
Abstract Background The prevalence of asthma in industrialized countries has been increasing dramatically and asthma is now the most common chronic disease of children in the United States. The rapidity of the increase strongly suggests that changes in environmental exposures are the likely cause of this epidemic. Further, the early onset of allergic manifestations suggests that these exposures may act on the prenatal development of the immune system. We have focused on the potential effects of bisphenol A (BPA), a chemical pollutant with one of the largest productions, on the development of childhood asthma. We have reported that perinatal BPA exposure promotes the development of allergic asthma in a mouse model. The current study was designed to identify a critical period of BPA exposure and to begin elucidating the mechanisms for this susceptibility. Methods Female BALB/c mice received 10 micro g/ml BPA in their drinking water from one week before pregnancy until the end of the study. Some of the pups were transferred in the first 48 h of life from their BPA-loaded mother to an unexposed mother, or vice versa. Half of the pups were sensitized with a low dose of the experimental allergen ovalbumin (OVA), the rest received PBS as an unsensitized controls. On day 22, the pups were challenged by inhalations of ovalbumin or PBS followed by quantification of eosinophils in and hyperreactivity of their airways, major indicators of experimental asthma in this classical mouse model. Hepatic expression of two isoforms of UDP-glucuronosyltransferase (Ugt) was quantified by quantitative RT-PCR at various ages. Results Pups exposed to BPA in utero and through breast milk, or in utero only, displayed an asthma phenotype in response to their "suboptimal" allergic sensitization, whereas, pups only exposed to BPA postnatally from breast milk, did not. The expression of Ugt2b1, an isoform related to BPA clearance in rats, was not detectable in mouse fetuses and newborn pups, but increased by day 5 and approached adult levels by day 25. Conclusions Prenatal exposures that produce environmentally relevant burdens of BPA, followed by postnatal allergic sensitization and challenges, promote the development of experimental allergic asthma. Delayed expression of BPA-metabolizing enzymes may explain, at least in part, the enhanced fetal susceptibility to this common environmental contaminant.